СРАВНИТЕЛЬНЫЙ АНАЛИЗ СВОЙСТВ ЦЕЛЛЮЛОЗЫ, ПОЛУЧЕННОЙ ИЗ ДРЕВЕСИНЫ ОЛЬХИ СЕРОЙ И ИВЫ ДРЕВОВИДНОЙ ... : COMPARATIVE ANALYSIS OF THE PROPERTIES OF CELLULOSE OBTAINED FROM GRAY ALDER AND WILLOW WOOD ... - Карабан, Алексей; Парамонов, Андрей; Севастьянова, Юлия; Медведев, Василий; Скорнякова, Анастасия; Третьяков, Сергей; Цветков, Илья; Коптев, Сергей; Богданов, Александр (ООО Цифра, 2025)
Ольха серая и ива древовидная входят в число лесообразующих пород Архангельской области. Для рационального и комплексного использования древесины данных пород необходимы исследования о бумагообразующих свойствах целлюлозы. В статье приведены результаты изучения сульфатной варки щепы ручного изготовления, полученной из ольхи серой и ивы древовидной.Цель работы – сравнительная характеристика бумагообразующих свойств целлюлозы, полученной из древесины лиственных пород, таких как ольха серая и ива древовидная. В лабораторных условиях проведено промышленное моделирование сульфатной варки на производственном белом щелоке щепы ольхи серой и ивы древовидной, подготовленной вручную из предоставленных образцов. Проведя физико-механические испытания на отливках из целлюлозы предоставленных образцов древесины, были получены результаты, проанализированы и соотнесены с аналогичными показателями целлюлозы из смеси берёзы и осины. Установлено, что бумага из ольхи серой образцов 2021 года, ольхи серой 2023 и ивы древовидной ... : Grey alder and arborescent willow are among the forest-forming species of the Arkhangelsk region. For the rational and comprehensive use of wood of these species, research on the paper-forming properties of cellulose is necessary. The article presents the results of a study of sulphate cooking of hand-made chips obtained from grey alder and arborescent willow.The purpose of the work is a comparative characteristic of the paper-forming properties of cellulose obtained from deciduous wood such as grey alder and arborescent willow. In laboratory conditions, industrial modeling of sulphate cooking on industrial white liquor of grey alder and arborescent willow chips prepared manually from the provided samples was carried out. After conducting physical and mechanical tests on castings from cellulose of the provided wood samples, the results were obtained, analyzed and correlated with similar indicators of cellulose from a mixture of birch and aspen. It was found that paper made from grey alder of 2021, grey alder ...